Improved rolling contact fatigue performance of selective electron beam melted Ti6Al4V with the as-built surface using induction-heating assisted ultrasonic surface rolling process - Liu, Zhongqiang; Liu, Xiao; Liu, Ruiping; Xiao, Zhiyu; Sanderson, Joseph (Applied surface science, 2023)
[Display omitted] •IH-USRP can further improve the surface integrity of samples.•Different kinds of oxides were induced by IH-USRP.•The RCF performance was greatly promoted by 196% using IH-USRP. In this paper, the effects of induction-heating assisted surface ultrasonic rolling processing (IH-USRP) on the rolling contact fatigue (RCF) performance of selective electron beam melting (SEBM) built Ti6Al4V was evaluated with respect to surface integrity, chemical composition, and microstructure were investigated. At the room temperature (RT), the surface roughness and line roughness (Ra and Rz) of the USRP treated sample are reduced by 92 % and 95 %, 78 %, and 66 % compared to the untreated sample, respectively, and the surface hardness is also increased by 17 %. The surface quality and hardness are further improved when samples treated by IH-USRP, and the oxide mixture could be found on the sample surface. The surface roughness and line roughness (Ra and Rz) of the IH-USRP treated sample at 650 °C were reduced by 96 % and 98 %, 85 %, and 83 %, respectively, while the surface hardness was 33 % higher than that of the untreated one. The surface quality improvement reduces the stress concentration, and the increased surface hardness means higher critical shear stress, which promotes the average RCF life by 196 %.